2018
DOI: 10.1002/jgf2.216
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of methicillin‐resistant Staphylococcus aureus in an acute care hospital in Japan

Abstract: BackgroundAsymptomatic carriers of methicillin‐resistant Staphylococcus aureus (MRSA) are important sources of nosocomial transmission. However, the route of transmission of MRSA is not completely understood. The purpose of this study was to calculate MRSA transmission rates in a hospital with a high MRSA infection/colonization density and inadequate hand hygiene compliance.MethodsThe prevalence of MRSA colonization among 157 patients at the time of admission to and discharge from a medical school hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Methicillin‐resistant Staphylococcus aureus colonization was investigated in 45 healthcare professionals. The results were compared with previous MRSA surveillance data and are summarized in Table . The proportion of MRSA colonization was significantly higher among healthcare professionals (11.1%) than community residents (0.72%; P < 0.0001) or admission case (2.5%; P = 0.018).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Methicillin‐resistant Staphylococcus aureus colonization was investigated in 45 healthcare professionals. The results were compared with previous MRSA surveillance data and are summarized in Table . The proportion of MRSA colonization was significantly higher among healthcare professionals (11.1%) than community residents (0.72%; P < 0.0001) or admission case (2.5%; P = 0.018).…”
Section: Resultsmentioning
confidence: 98%
“…Multilocus sequence typing analysis revealed that five isolates from healthcare professionals consisted of two ST8 and three ST764 isolates. These results were combined with previous MRSA surveillance data and are summarized in Table . Both ST8 and ST764 strains were isolated from residents, admission cases, hospitalized patients, and healthcare professionals.…”
Section: Resultsmentioning
confidence: 99%
“…Además, Tuta et al (2019), en Nigeria, encontraron que entre 300 niños que asistían a la consulta externa, el 36,3% estaba colonizado por S. aureus y el 5,3% eran SARM. De igual manera, Matsumoto et al (2018), en Japón, en un hospital con una alta densidad de infección, en 157 pacientes encontraron que S. aureus resistente a la meticilina prevaleció en el 1,9% de ellos. De modo idéntico, Marbou et al (2020), en Camerún, en muestras fecales en sujetos hospitalizados con síndrome metabólico, encontraron que en 30 de estos pacientes se detectó S. aureus, de los cuales la prevalencia del SARM fue del 79,82%, mientras que SASM fue del 20,17%.…”
Section: Fajardo and Gainesunclassified
“…So much so that hospitals now need to classify whether a patient has a regular staph infection or MRSA (methicillin resistant staph infections). There has been a drastic increase in antibiotic resistant staph infection hospitalizations [3,12] over the past decade and I believe that a solution to MRSA infections might be found in QS mechanisms. A study published by the American society of bacteriology has shown direct correlation between QS and the maturation of biofilm in staphylococcus aureus; "QS via the agr system works to regulate S. aureus biofilms" [9].…”
Section: Research and Problemmentioning
confidence: 99%